Ibn Rushd’s Rationality as an Effort to Combat Superstition: An Epistemological Analysis of Islamic Thought - Alpin Harianto (Afkaruna: International Journal of Islamic Studies (AIJIS), 2026)
This article examines Ibn Rushd’s rationality as an epistemological strategy in combating superstition (khurafat) within the Islamic intellectual tradition. The main issue addressed is the persistence of religious practices and beliefs that lack a solid rational and epistemic foundation, often sustained through blind taqlid, textual literalism, and methodological errors in understanding revelation. This phenomenon highlights the urgency of reintroducing a rational framework for a responsible interpretation of Islamic teachings. The study aims to analyze Ibn Rushd’s concept of rationality, particularly the status of reason, the burhan method, and his critique of irrational patterns of religiosity, as well as to assess its relevance in the contemporary Islamic context. This research employs a qualitative library-based method using an epistemological and historical-philosophical approach to Ibn Rushd’s major works and recent academic studies. The findings indicate that Ibn Rushd’s rationality does not stand in opposition to revelation; rather, it functions as an instrument for purifying religion from distortion and superstition. By positioning reason as a means of verifying religious understanding, Ibn Rushd offers a model of religiosity that is critical, moderate, and intellectually responsible. This article contributes to strengthening rational Islamic thought as a constructive alternative in responding to contemporary religious challenges.